2015
DOI: 10.1186/s13104-015-1452-x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Anti-tuberculosis treatment and treatment outcomes among tuberculosis patients in Alamata District, northeast Ethiopia

Abstract: BackgroundNon-adherence to tuberculosis (TB) treatment can result in an emergence of new strains, prolonged infectiousness, drug resistance and poor treatment outcomes. Thus, assessment of the level of adherence to anti-TB treatment, treatment outcomes and identifying factors associated with non-adherence and poor treatment outcomes are vital for improving TB treatment adherence and treatment outcomes in the study area. The main objectives of the current study were to assess the level of adherence to anti-TB t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
140
9
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(179 citation statements)
references
References 26 publications
19
140
9
11
Order By: Relevance
“…Similar findings were reported from previous studies in Ethiopia [13] [15] [31]. Evidence also indicates that less proportion of EPTB cases compared to other forms of TB were observed in other studies conducted in Ethiopia [14] [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar findings were reported from previous studies in Ethiopia [13] [15] [31]. Evidence also indicates that less proportion of EPTB cases compared to other forms of TB were observed in other studies conducted in Ethiopia [14] [16].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, despite the high treatment success rate of new PTB+ ve cases, the overall cure rate was 72.1%, which is lower than previous cure rate reports of 85.5% from Northern Ethiopia [12] and 81.1% in North West Ethiopia [31]. Sputum smear examination at two, five and seven months is recommended as part of anti-TB treatment follow up.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Cases on retreatment were twice as likely to default treatment relative to their newly diagnosed counterparts. Studies in Morocco 13,41,42 [ 8 _ T D $ D I F F ] and Ethiopia, 43 and in the Eastern Cape, KwaZulu-Natal, and Eastern Cape Provinces of South Africa 44 have reported similar findings. In the South African study, self-reported reasons for defaulting included self-perceived improved health, and structural and psychosocial problems.…”
Section: Discussionmentioning
confidence: 68%
“…There was a high level of adherence to anti-TB treatment and also a high TB treatment success rate. 4 Countries implementing DOT to ensure treatment adherence have shown impressive results with increasing treatment success and low default rates. 1,5,6 India has had an ongoing National TB Program (NTP) since 1962.…”
Section: Introductionmentioning
confidence: 99%